A Study of necessity of episiotomy in primigravida - Saeid, Muhabat S.; Muhammad, Atiya K; Mohamed, Nokhsha R. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This prospective study has been carried out in Sulaimani Maternity Teaching Hospital, from October 2006 to April 2007 to evaluate the outcome of those primigravida women delivered vaginally without epiotomy who had not undergone episiotomy. Purposive sample of (152) low risk primigravida women in the labour ward during 2nd stage of labour has been selected to collect data properly. It should be noted that previous perineal operation, malposition, instrumental delivery, premature babies, fetal distress, pelvic deformities, induction of labour , short or rigid perineum, medical problems (like hypertension, diabetes, and heart disease...ect), and have been excluded. Questionnaire has been utilized as study institute, observations, checking &follow up for 24 hours, 1 week, 6 weeks have been used to achieve the main goals. Through this study it was found that 34.9% of cases remain with intact perineum, 42.8% of cases had 1st degree p. tear, 22.4% of cases had 2nd degree p. tears, and only 83 cases (54.6%) needed suturing (49 cases with 1st degree tears &34 cases with 2nd degree tears). It was noted also that complications in 1s 24 hours & after 1 week was less common in patients who had intact perineum. On the bases of this study, we recommend that episiotomy should be restricted to specific maternal or fetal conditions &routine use of episiotomy should be abandoned.
Keywords: Episiotomy; Primigravida